Analisis Sentimen Layanan Jasa Pengiriman Pada Ulasan Play Store: Systematic Literature Review - Dellavianti Nishfi (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
Sentiment analysis is a tool that assists in mining opinions and capturing expressions of individuals when analyzing their emotions generated from decisions, whether unfair of fair, when accompanied by personal sentiment. The courier service company has broad access in Indonesia and caters to various types of deliveries, driving research based on classifying reviews based on positive, negative, or neutral sentiments using user review data from the Google play store. This research utilizes the Systematic Literature Review method and discusses the result of sentiment levels. Furthermore, the analysis reveals that factors such as delivery speed, timeliness, and service quality are the most common consumer complaints. The findigns of this paper compile published maaterials regarding courirer service companies and opinions from netizen reviews. Journals collected span from 2015 to 2023. It is hoped that this research will be beneficial and serve as a reference for consumers in choosing a courier service company that suits their needs.